Preliminary Investigation of the Reliability and Validity of the Clinical Perfectionism Questionnaire in a Clinical Sample - Hoiles, K.; Kane, R.; Watson, H.; Rees, C.; Egan, Sarah (Australian Academic Press Pty Ltd, 2016)
Perfectionism is a risk and maintaining factor across psychopathology and has been proposed to be a transdiagnostic process. The aim of this study was to examine the reliability and validity of the Clinical Perfectionism Questionnaire (CPQ) in 32 adults (75% female, M age = 35.54 years, SD = 9.71) with a range of psychological disorders, presenting for treatment of clinical perfectionism. There was evidence that the CPQ was correlated with established measures of perfectionism and theoretically related constructs including self-criticism and dichotomous thinking. The CPQ was also able to predict treatment outcome. The internal consistency was not adequate in the current study; however, the sample size was small. Future studies should examine the psychometric properties of the CPQ in a larger sample of individuals with a range of psychological disorders.